Alien Plants between Practices and Representations : The Cases of European Spruce and Beach Rose in Finland - Uusitalo, Harri; Lähdesmäki, Heta; Sonck-Rautio, Kirsi; Latva, Otto; Salmi, Hannu; Alenius, Teija (The White Horse Press, 2025)
In Finland, the European spruce (Picea abies) and the beach rose (Rosa rugosa) have very different cultural resonances and ramifications, but they also have many similarities. In this study, we examine these species through the concept of ‘plantiness’ to reveal the political ecology behind the categories of native and alien, demonstrating the national and biological belonging of said species. We ask why people want to protect certain species and not others – which ultimately amounts to deciding which plants are permitted to exist and which are not. Acknowledging that natural changes occur constantly, we also ask how people come to decide what counts as the ‘status quo’ that should be protected. We create a synthesis from our disciplines: palaeoecology, which focuses on the ecology of the past; cultural history and ethnology, which explore historical and contemporary times; and linguistics, which focuses on a long time period from prehistoric to contemporary times.